A Systematic Review of Seven Core Quality Control Tools and Their Applications in Manufacturing Process Improvement - Ayenigba, Alfred Ayo; Afariogun, David Adebisi; Aina, Oluwaseun Ayomiposi (International Journal of Education, Management, and Technology, 2025)
This paper provides a comprehensive analysis of the seven basic quality control tools and their applications in addressing problems within manufacturing industries. The tools examined include cause-and-effect diagrams, check sheets, control charts, histograms, Pareto charts, scatter diagrams, and flowcharts. Each tool is discussed in detail, focusing on its purpose, theoretical foundations, and practical applications in quality management. The study emphasizes how these tools support systematic identification, analysis, and resolution of production challenges, thereby improving process efficiency, reducing defects, and enhancing overall product quality. By demonstrating their versatility and effectiveness, the paper highlights the relevance of these tools as essential components of continuous improvement strategies in modern manufacturing.